Les Autochtones au Canada: espaces et peuples en mutation - Desbiens, Caroline; Hirt, Irène (L'Information géographique, 2012)
Alors que les questions relatives à l’autochtonie ont longtemps été le domaine de l’anthropologie, nous assistons ces dernières années à un décloisonnement des recherches. La géographie participe activement à cette mouvance, notamment par la richesse de sa boîte à outils en ce qui concerne les questions de paysage, ressources, environnement et gouvernance territoriale. En commençant par un survol des aires culturelles autochtones en Amérique, nous proposons dans cet article d’identifier trois thèmes dominants en ce qui a trait aux espaces de l’autochtonie contemporaine au Canada : la gouvernance, les savoirs, et l’urbanité.
Keywords: amériques; approches et analyses; cours; discipline; géographie; har4600; histoire et politique; pol4105; premier cycle; premières nations; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres